2020
DOI: 10.1017/s1751731120001688
|View full text |Cite
|
Sign up to set email alerts
|

Review: Use and misuse of meta-analysis in Animal Science

Abstract: In animal sciences, the number of published meta-analyses is increasing at a rate of 15% per year. This current review focuses on the good practices and the potential pitfalls in the conduct of meta-analyses in animal sciences, nutrition in particular. Once the study objectives have been defined, several key phases must be considered when doing a meta-analysis. First, as a principle of traceability, criteria used to select or discard publications should be clearly stated in a way that one could reproduce the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 53 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…It can be used as a prospective tool to study P digestibility for different feedstuffs and feeding strategies, as well as the effect of specific digestive processes on P digestive utilization. Second, given the large number of publications on P digestibility in pigs, meta-analysis, a statistical method relevant for summarizing and quantifying knowledge acquired through previously published research ( 73 , 74 ), was chosen to predict P digestibility considering dietary P forms, Ca, and exogenous phytases. Dietary forms are PP and NPP from plant, mineral, and animal ( 72 ).…”
Section: Precisely Assess Bioavailability and Evaluating The Nutritional Values Of Feed Ingredientsmentioning
confidence: 99%
“…It can be used as a prospective tool to study P digestibility for different feedstuffs and feeding strategies, as well as the effect of specific digestive processes on P digestive utilization. Second, given the large number of publications on P digestibility in pigs, meta-analysis, a statistical method relevant for summarizing and quantifying knowledge acquired through previously published research ( 73 , 74 ), was chosen to predict P digestibility considering dietary P forms, Ca, and exogenous phytases. Dietary forms are PP and NPP from plant, mineral, and animal ( 72 ).…”
Section: Precisely Assess Bioavailability and Evaluating The Nutritional Values Of Feed Ingredientsmentioning
confidence: 99%
“…Meta-analysis originated from medical science and is widely accepted in animal science for development of empirical nutrition models, which may help to understand a complex system or make predictions (Sauvant et al, 2019). The minimum number of studies required for a meta-analysis is a common question among scientists.…”
Section: Total Fa Digestion In Dairy Cowsmentioning
confidence: 99%
“…In addition, differences in research design, statistics, animal breed, and other technical conditions can produce variation in experimental results. These challenges can be overcome with the use of meta-analysis, a thorough statistical procedure for analyzing a combined dataset obtained from multiple research experiments [7,8]. Sauvant et al [7] reported that many publications conducted meta-analysis of N supplementation and proved it widely accepted, especially in ruminant nutrition.…”
Section: Introductionmentioning
confidence: 99%